Throwing a Toy Wrench in the “Greatest Legal Engine”: Child Witnesses and the Confrontation Clause - Jonathan Clow (Washington University Law Review, 2015)
Cross-examination of witnesses has often been called the “greatest legal engine ever invented for the discovery of truth.” Enshrined in the Confrontation Clause of the Sixth Amendment, this most basic feature of an adversarial legal system guarantees criminal defendants the right to have the prosecution’s witnesses testify in open court and the opportunity to question said witnesses in front of the jury. The premise underlying this “greatest legal engine” is challenged, however, when children are the “witnesses against” the defendant. Social science and psychological research in recent decades suggest that cross-examination of child witnesses could actually interfere with the discovery of truth. A lesser capacity for recalling past events, a lack of understanding of the criminal justice system, suggestibility, and the trauma of testifying in court all raise concerns about the accuracy of child testimony compared to that of adults. While cross-examination can be used to elicit the truth from adversary witnesses, the same suggestive techniques could manipulate vulnerable children to testify to just the opposite. This Note explores this contradiction: the Confrontation Clause, constitutionalizing the right of cross-examination to ensure that convictions are based solely on accurate and reliable testimony, requires, if read literally, that child witnesses submit to a procedure which could undermine that very purpose. The history and purpose of the Confrontation Clause suggest that cross-examination is not required in those circumstances. In the case of child witnesses, modern Confrontation Clause jurisprudence should take into account public policy concerns regarding the development of children and permit the admission of hearsay—testimony regarding a child’s statements from someone other than the child—where cross-examination would not advance the fact-finding goals of a criminal trial. In short, children should not be treated as adults for purposes of confrontation. This Note does not propose doing away with cross-examination of child witnesses altogether and should not be read as minimizing the importance of cross-examination to American criminal justice. However, this Note makes the modest claim that the Constitution does not necessarily impose a categorical requirement that child witnesses, just as adults, testify and be subject to cross-examination. The Confrontation Clause, and the Constitution in general, does not require strict enforcement where its purpose would be undermined. This Note addresses the difficult balance to be struck between the value of cross-examination and risks of confronting child witnesses, and it explores other practical solutions to this problem.
Keywords: Confrontation Clause; Evidence; Child witnesses; Cross-examination; Sixth Amendment; Crawford v. Washington